FOMO-Based Marketing Strategies and Their Impact on Online Consumer Purchase Intention: A Study on Madura Island - Supriyanto Supriyanto; Irfan Azim (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of a Fear of Missing Out-based marketing strategy on online consumer purchase intentions on Madura Island. The FOMO phenomenon is increasingly used in digital marketing practices by creating perceptions of scarcity, time constraints, and social pressure, but empirical evidence in a non-metropolitan context is still limited. This study used a quantitative approach with a survey of online consumers on Madura Island. Data were collected through a structured questionnaire and analyzed using simple linear regression. Validity and reliability tests indicate that all research instruments meet the eligibility criteria. Classical assumption tests indicate that the regression model meets the assumptions of normality, does not contain multicollinearity, and is free from heteroscedasticity. The study findings indicate that a FOMO-based marketing strategy has a positive and significant effect on online consumer purchase intentions. The coefficient of determination indicates that FOMO can explain some of the variation in purchase intentions, while the remainder is influenced by factors outside the model. This study provides theoretical contributions in expanding digital marketing studies in the local context, as well as practical implications for MSMEs and digital marketers in designing effective, contextual, and ethical FOMO strategies.